Un nouvel indicateur de prédisposition au risque d’érosion côtière, application en Manche et en Vendée (France) - Martin Juigner (Unité Mixte de Recherche 8504 Géographie-cités, 2021)
Low sandy coasts are small and constrained spaces very sensitive to coastal hazards. The settlement of human activities next to the coastline sets up at-risk territories. The identification of territories exposed to coastal erosion is one of the objectives of the French national strategy for integrated coastal management initiated by the French Ministry of Ecology. This national strategy relies on the network of regional coastal observatories. This paper proposes a common geomatics approach of two of these regional observatories aimed at spatializing a new coastal erosion risk indicator. The partnership between the "Réseau d’observation du littoral de Normandie et des Hauts-de-France" and the "Observatoire régional des risques côtiers en Pays de la Loire", aims at applying this indicator along the sandy coasts of western Manche and northern Vendée, France. The indicator is composed of the combination of 3 variables into spatial units (“boxes”): (i) the historical shoreline change, (ii) the distance between the shoreline and the buildings, roads and campsites located in the 100-m coastal strip and (iii) the presence/absence of coastal protections. The computation of the indicator for each stake, at the scale of the territories, allows the ranking of the erosion risk territories